Analysis of Politeness Maxims Found in Lady Chatterley’s Lover Movie - Ni Made Sri Maheswari Paramitha; Komang Dian Puspita Candra (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
Politeness has always been one of the primary linguistics issues. The objectives of this research were centered on identifying the varieties of politeness maxims utilized by characters in the 2022 adaptation of the film